Changes in bone mineral density over time in patients with self-reported chronic diseases: The Tromsø Study - Bhandari, Anita (UiT Norges arktiske universitet, 2014)
Objective: To examine the total hip (TH) and femoral neck (FN) bone loss in women and men above 50 years of age with self-reported chronic diseases. Methods: Using data from ‘The Tromsø Study’, men and women aged 50-74 years were included in this study. Disease status was identified based on self-reports. Bone mineral density (BMD) of TH and FN were measured using DXA (Dual-energy X-ray Absorptiometry). The change in BMD was calculated as the difference between BMD in Tromsø 5 and Tromsø 6. Linear regression analysis was used to assess relationship between the predictor variables (diseases) and the outcome (change in total hip and femoral neck BMD). Results: Out of 2310 participants, 860 were men and 1450 were women. Men had significantly more cases of heart disease (p<0.0001) and stroke compared to women, (p=0.036) whereas, hypothyroidism was more frequent among women (p<0.0001). Significantly higher levels of baseline TH and FN BMD were measured in men than women (p<0.0001). A significant annual percentage change in TH BMD among women with CVD (-0.23%; p=0.019) and hypothyroidism (-0.1%; p=0.041) was observed in models adjusted with several common risk factors. The annual percentage change in FN BMD was significant among men with stroke (-0.46 %; p=0.012). Conclusion: The results of this study indicate that self-reported chronic diseases are associated with increased deterioration of BMD in elderly men and women. Bone loss was evident in women with CVD or hypothyroidism, and in men with stroke. This highlights the need of careful evaluation of elderly patients with chronic diseases with respect to BMD and thereby fractures risk.